Efficacy of Intranasal Fluticasone Nasal Spray Alone Versus Intranasal Fluticasone Combined with Oral Montelukast and Levocetirizine in Treatment of Allergic Rhinitis–A Randomized Control Trial. - Mohamed Afsal Y; Chandrashekharayya S Hiremath (International Journal of Medical Students)
BACKGROUND: Allergic Rhinitis (AR) is characterized by an immunological response facilitated by IgE antibodies inside the nasal mucosa, which is initiated upon exposure to allergens present in the air. The illness under consideration is characterized by symptoms including the presence of watery nasal discharge, nasal congestion, sneezing, and nasal itching. It affects between 10 and 40 per cent of the global population, which affecting the quality of life of many persons. Hence, the requirement of a treatment targeted at delivering maximum symptom control and has minimum to nil adverse effects. AR symptoms impair cognitive function, which can be further exacerbated by the use of widely available first-generation antihistamines.